(untitled) (Proceedings of International Conference on Special Education, 2015)
Empowerment is a multidimensional social process that helps people gain control over their own lives. It is a process which fosters that ability in every individual which they can use in their own lives and their communities by acting on issues which are socially defined as important. Empowerment of individuals with disability is quite a complex task and requires attitudinal change of the society as a whole. The first step in this regard should be ensuring education of children with special needs. The democratic systems all over the world are also equally wedded to the idea of providing equal educational opportunity to every individual without any sort of discrimination especially on grounds of disability. Inclusive education represents the latest trend in the provision of placement in the field of education for children with special needs. Through the present study the researcher has made an attempt to study the system of Inclusive education and the initiatives taken by the Government in Kolkata, a metropolitan city in India. Government officers were interviewed to collect data in this regard. Semi – structured questionnaires were used and the data, in the form of detailed responses were analyzed qualitatively only. It was found that the Government took some initiatives in providing education to children with special needs by providing funds to general schools. However, lack of inclusive schools in the city was quite evident. The present emphasis on inclusive education all over the world underlines the need and importance of this study